A more precise way to assess the success of the president's legislative agenda: the success of presidential priority bills in Chile, 1990–2018. Issue 2 (17th February 2023) - Jaime-Godoy, Jhon; Navia, Patricio
ABSTRACT: The legislative success of a president is normally measured with respect to president-initiated bills. However, when they control the legislative agenda, presidents can also prioritize legislator-initiated bills and take credit for their passage. We contend that presidential legislative success should be measured with respect to both types of bills. With data on the 10301 bills introduced in Chile (1990–2018), we analyze the determinants of success of the 2640 presidential priority bills (PPB) – president-initiated bills and legislator-initiated bills that received a presidential priority motion to speed up debate. Reforms that strengthened the legislature have induced the executive to prioritize more legislator-initiated bills. PPB introduced in the first year of the term are more likely to pass while those introduced after the 2005 reforms and in the last year of the term are less likely to pass. Presidential approval, majority support in congress and Finance or Constitution Committee referrals are not good predictors of the success of PPB. The determinants better explain the passage of president-initiated bills than the passage of legislator-initiated bills.